The canary and the crucible: Fiji’s climate stewardship and a blueprint for planetary resilience - Khan, Shifadjzic; Yun, Byung-Wook; Sachan, Hirdesh Kumar; Krishna, Deeksha (Frontiers in Climate, 2025)
At the razor’s edge of the Anthropocene, Fiji offers the world not a plea for help, but a masterclass in survival: turning existential threat into a radical blueprint for planetary endurance. This review interrogates Fiji’s holistic climate resilience framework as a frontline small island developing state. The central research question asks: How has Fiji integrated national legislation, catalytic climate finance, rights-based mobility, and strategic diplomacy to construct a comprehensive governance model, and to what extent can this emergent architecture serve as a transferable blueprint for anticipatory adaptation in the Anthropocene? A systematic synthesis of scientific literature, policy texts, and institutional reports deconstructs Fiji’s multi-scalar response into a coherent conceptual model. The analysis advances the “Archipelagic Resilience Model,” structured around four interdependent pillars. Geopolitical Acupuncture leverages Fiji’s moral authority to exert influence in global climate governance. Braided Resilience entwines indigenous ecological knowledge, particularly the Vanua worldview, with contemporary climate science. Catalytic Finance mobilizes resources through innovative mechanisms such as sovereign blue and green bonds. Socially-Just Climate Mobility pioneers a rights-based relocation framework that safeguards dignity and cultural continuity. While innovative, this model exposes tensions, including the development–adaptation paradox and risks of maladaptation. By articulating both synergies and contradictions, the study reframes Fiji as a norm entrepreneur and blueprint for planetary resilience. It establishes a forward-looking research agenda to quantify braided systems and scale equitable adaptation pathways in vulnerable contexts.